PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP MOTIVASI BERPRESTASI PEGAWAI SEKRETARIAT BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PERHUBUNGAN - Widiah Nur Wahyuni (Universitas Negeri Jakarta, 2016)
The objective of this research is to obtain information about the effect of transformational leadership and job satisfaction on employee achievement motivation of Badan Pengembangan Sumber Daya Manusia Perhubungan. It was quantitative research with survey method in Badan Pengembangan Sumber Daya Manusia Perhubungan. The research was conducted to all employees of Badan Pengembangan Sumber Daya Manusia Perhubungan by using a survey method with path analysis applied in testing hypothesis. The number 89 employees as sample was selected by using Slovin formula. The research conlude: (1) There is a direct positive effect of transformational leadership on achievement motivation. (2) There is a direct positive effect of job satisfaction on achievement motivation. (3) There is a direct positive of transformational leadership on job satisfaction.